Soup For Lunch - Salzano, Tammi; Avgustinovich, Irina ([Place of publication not identified] : Clever Publishing, 2022)
In this humorous, imaginative story, a young boy falls asleep after enjoying a warm, comforting bowl of soup with his mom and sister--and discovers that his sister's bowl of soup has somehow flooded the house!
New Kids Book 2022 Winter.